2020
DOI: 10.14202/vetworld.2020.549-555
|View full text |Cite
|
Sign up to set email alerts
|

The influence of electromagnetic radiation of cell phones on the behavior of animals

Abstract: Background and Aim: The radiation emitted from cell phones has various deleterious effects on human health. The article considers the problem of the effects of electromagnetic radiation (EMR) of cell phones on the behavior of animals. The use of mobile phones is continually increasing throughout the world. All of the world population uses mobile phones widely; thus, having strong and daily effect on the brain. There is no restriction on the use of mobile phones. Getting more advantages and convenience … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…The nervous system is one of the most sensitive target of microwave radiation. Experimental studies show that exposure to microwave may lead to headache, sleep disorder, changes in EEG and cognitive function (1)(2)(3). And the research on the effect of microwave radiation on cognitive function has lasted for decades, but it is still controversial and the associated mechanisms remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The nervous system is one of the most sensitive target of microwave radiation. Experimental studies show that exposure to microwave may lead to headache, sleep disorder, changes in EEG and cognitive function (1)(2)(3). And the research on the effect of microwave radiation on cognitive function has lasted for decades, but it is still controversial and the associated mechanisms remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The use of the mobile phone has raised concerns in the environment (2), human health (3) and cognitive functions (4). It also affects animal behavior (5). Similar to humans and animals, it also affects plants (6).…”
Section: Introductionmentioning
confidence: 99%
“…According to WHO, EMW pollution is defined one of the most common problems of human and environmental health [2; 3]. In fact, studies have shown that the exposure to EMW can affect liver, kidneys and nervous system [3][4][5].…”
Section: Introductionmentioning
confidence: 99%